Waiting for antichrist charisma and apocalypse in a Pentecostal church - Thompson, Damian 1962- (Oxford New York Oxford University Press, 2005)
Damian Thompson looks at the members of one religious group with a strong apocalyptic tradition, Kensington Temple, a large Pentecostal church in London, & attempts to understand how they reconcile doctrines of the end of the world with the demands of their everyday lives
The problem of the endPentecostalism and the end times -- Kensington Temple -- Living with the end -- Millenarians -- The year 2000 -- Conclusions.
Includes bibliographical references (p. [195]-207) and index
Online-Ausg.
Keywords: Millennialism; Pentecostal Churches -- Doctrines